The bridges of Robert Adam a fanciful and picturesque tour - Riley, Benjamin (Triglyph Books, 2023)
"The bridge has always stood as a transitional structure--not purely a work of engineering, nor simply a work of architecture. Its functional requirements are more stringent than those of the average building: it not only must stand up; it must stand up, support those who cross it, and effectively span the space over which it stands. As Samuel Johnson said, 'the first excellence of a bridge is strength...for a bridge that cannot stand, however beautiful, will boast its beauty but a little while.' The Scottish architect Robert Adam (1728-92) understood these precepts well, continually building bridges that were not just structurally sound, but also aesthetically pleasing. Unlike his contemporaries, Adam did not view bridges as mere skeletons upon which to apply ornament. Rather, he sought to achieve architectural totality, incorporating his bridge designs into grater architectural programs, thereby producing aesthetically pleasing and contextually specific designs"--Back jacket flap
Literaturverzeichnis: Seite 138-145
Keywords: Adam, Robert -- 1728-1792; Brückenbau; Großbritannien; Adam, Robert / 1728-1792; Adam, Robert - 1728-1792 / (OCoLC)fst00011921; 1700-1799; Bridges / Great Britain / 18th century; Architecture / Great Britain / 18th century; Architects / Great Britain / 18th century; Neoclassicism (Architecture); Architects / (OCoLC)fst00813114; Architecture / (OCoLC)fst00813346; Bridges / (OCoLC)fst00838671; Neoclassicism (Architecture) / (OCoLC)fst01035766; Great Britain / (OCoLC)fst01204623